HCV: The Journey from Discovery to a Cure Volume II - Sofia, Michael J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Hepatitis C is a liver disease caused by the hepatitis C virus (HCV) and infects approximately 75 million individuals worldwide. It is also one of the major causes of liver cancer and liver transplants. The elucidation of the HCV genome, and the development of a whole cell system to study the virus spurred the search for novel direct acting antiviral drugs to cure this disease. This global effort culminated in the development of direct acting antiviral drugs that led to cure rates approaching 100% in all patient populations after only 8-12 weeks of therapy. These efforts resulted in one of the greatest achievements in public health and provides the potential for eliminating HCV as a major disease worldwide. This volume is aimed at a broad audience of academic and industrial scientists interested in the discovery and development of drugs to treat viral diseases and those interested in reading about one of the most unique accomplishments in biomedical research. The volume will provide a one of a kind reference work that highlights the many efforts, from the discovery of the HCV virus, to the invention of breakthrough medicines and their use in the real world to cure patients. It is the companion book to the volume "HCV: The Journey from Discovery to a Cure - Volume I".
NS5A as a target for HCV Drug Discovery -- The Discovery and Development of Daclatasvir: An Inhibitor of the Hepatitis C Virus NS5A Replication Complex -- The Discovery of Ledipasvir (GS-5885): The Potent Once-Daily Oral HCV NS5A Inhibitor in the Single-Tablet Regimen Harvoni® -- The Discovery of Velpatasvir (GS-5816): The Potent Pan-Genotypic Once-Daily Oral HCV NS5A Inhibitor in the Single-Tablet Regimens Epclusa® and Vosevi® -- Discovery of Elbasvir -- HCV NS5A as an Antiviral Therapeutic Target: From Validation to the Discovery and Development of Ombitasvir and Pibrentasvir as Components of IFN-Sparing HCV Curative Treatments -- Evolution of HCV NS4B Inhibitors -- The Evolution of Clinical Trials for Hepatitis C -- The Clinical Development of Ledipasvir/Sofosbuvir (LDV/SOF, Harvoni®) -- The Clinical Development of Sofosbuvir/Velpatasvir (SOF/VEL, Epclusa®) -- The Clinical Development of Sofosbuvir/Velpatasvir/Voxilaprevir (SOF/VEL/VOX, Vosevi®) -- Clinical Development of Viekira Pak to Mavyret -- Development of ZEPATIER® -- Real world effectiveness of DAA therapies -- The Benefit of Direct-Acting Antiviral HCV Cure Therapies -- Cure and Control: What Will It Take to Eliminate HCV? -- Perspectives on HCV Cure.
Keywords: Medicinal chemistry; Virology; Clinical biochemistry; Bioorganic chemistry; Pharmaceutical chemistry; Medicinal Chemistry; Virology; Medical Biochemistry; Bioorganic Chemistry; Pharmaceutics